2022
DOI: 10.21203/rs.3.rs-2300112/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compound Dihuang Granule Changes Gut Microbiota of MPTP-Induced Parkinson's Disease Mice via Inhibiting TLR4/NF-κB Signaling

Abstract: Intestinal flora was connected to Parkinson's Disease (PD) pathology. The ancient Chinese medication for PD is Compound Dihuang Granule (CDG), and we found a neuroprotective function in treating the constipation of PD patients. Nevertheless, the mechanism of action still needs to be clarified. We predicted the probable targets of CDG against PD through Traditional Chinese medicine (TCM) network pharmacology and verified the analysis through animal experiments in vivo. The protein-protein interaction (PPI) netw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…Traditional Chinese medicine (TCM) has been used for the treatment of dyskinesia corresponding to the clinical manifestations of PD for more than two thousand years [7][8][9][10]. In recent years, pharmacological studies of traditional Chinese medicine have shown that traditional Chinese medicine has shown potential clinical e cacy in alleviating PD symptoms [11][12][13][14].…”
Section: Bacgroundmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has been used for the treatment of dyskinesia corresponding to the clinical manifestations of PD for more than two thousand years [7][8][9][10]. In recent years, pharmacological studies of traditional Chinese medicine have shown that traditional Chinese medicine has shown potential clinical e cacy in alleviating PD symptoms [11][12][13][14].…”
Section: Bacgroundmentioning
confidence: 99%